The Meaning of Pilgrimage (Hajj): Re-shaping the Pious Identity of Belgian Turkish Muslims - Toğuşlu, Erkan (Islam and Christian-Muslim relations, 2017)
This article examines how Belgian Muslims of Turkish origin interact with the hajj (pilgrimage) and the meaning of the pilgrimage for Muslims living in Belgium. It focuses upon the space of pilgrimage rituals, identifies the motivations for the practice of the pilgrimage and attempts to explain how the ‘canonical meaning’ of the hajj, which is considered unchanging, is adopted in the new Belgian situation and how pilgrims regard it. The physical practice of pilgrimage constitutes an interesting area through which to depict how Belgian Muslims of Turkish origin experience the sacred journey that shapes their religious understanding and their identity. The article’s findings are based on interviews and observations in 2012 and 2014. The author visited mosques during hajj information sessions and spoke with imams, but the fieldwork was carried out among pilgrims who had visited Mecca for their hajj and ʿumra..